2022
DOI: 10.3390/jcm11071958
|View full text |Cite
|
Sign up to set email alerts
|

Associations between Covariates and Pneumothorax Observations in CT-Guided Lung Biopsies

Abstract: The purpose of this study is to assess the effect of nine covariates on the occurrence or absence of stable or symptomatic pneumothorax. Forty-three patients underwent CT-guided lung biopsies from January 2020 to January 2022 (24 m, 19 f, median age 70 years). All the interventions were carried out with a semi-automatic 18G needle and a 17G trocar in a prone or supine position. Different covariates were measured and correlated to the rate and severity of the pneumothoraces observed. Nominal two-sided t-test p-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…All procedures were performed by the same operator. Various previous studies have evaluated the importance of the needle-pleura angle and its significance in the incidence of pneumothorax [3,6,[9][10][11]. A multivariate analysis by Hiraki et al involving 1098 patients found that a needle trajectory angle of <45 • (p = 0.014) was a significant risk factor for pneumothorax [9].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…All procedures were performed by the same operator. Various previous studies have evaluated the importance of the needle-pleura angle and its significance in the incidence of pneumothorax [3,6,[9][10][11]. A multivariate analysis by Hiraki et al involving 1098 patients found that a needle trajectory angle of <45 • (p = 0.014) was a significant risk factor for pneumothorax [9].…”
Section: Discussionmentioning
confidence: 99%
“…Several recent studies have highlighted the significance of the needle's angle in the pleura and the relationship between the right angle and the incidence of pneumothorax [4,6]. This paper aims to correlate the frequency and severity of pneumothorax to different needlepleura angles, allowing the operator to guide the needle through a safe zone with a lower risk of pneumothorax.…”
Section: Introductionmentioning
confidence: 99%